Implementasi Metode Secure Hash Algorithm-1 Untuk Mendeteksi Keaslian File Dokumen - Dermawan Lumban Toruan (Forum Kerjasama Pendidikan Tinggi (FKPT), 2021)
Document file is a means of transforming information from one person to another or from a group to another. The development of computerized technology has greatly increased. Document files are very vulnerable to fraud, eavesdropping or data theft by irresponsible parties. In order to maintain the security of document files, this can be done by using cryptographic techniques. Cryptography is the science of keeping data secure. Cryptography is one of the data security methods that can be used to maintain data authenticity, data confidentiality, and the authenticity of data transmission. SHA, which stands for Secure Hash Algorithm, is a standard hash function published by NIST (National Institute of Standards and Technology), (NIST, 1995a). This study will use the SHA-1 method to secure the authenticity of document files, document confidentiality, document integrity, and document authentication. This study describes the security process for detecting the authenticity of document files using the SHA-1 method in the form of detection so that confidential documents sent via public telecommunications cannot be changed or modified by unauthorized persons or unauthorized persons. This is done as an effort to minimize acts of fraud, hoaxes, or misuse of document files.